Modelo hidrogeológico conceptual del sistema acuifero potrero-Caimital, Nicoya, Guanacaste, Costa Rica - García, Pamela M. (2015)
The Potrero-Caimital aquifer system, located in the province of Guanacaste, has been defined as an unconfined aquifer composed of three layers: the top layer of sandy-clay soil, the layer of gravel and sand with a thickness approximately 20m, underlained by the layer of soil and weathered and fractured lavas, all located on the foundation developed in the Nicoya Complex. A model was obtained by the lithological information of 42 wells registered in SENARA.The study area has values of transmissivity (T) between 37-2824 m²/d and a range of hydraulic conductivity (K) between 2-175 m/d was defined. The hydraulic conductivity was increased toward the colluvium. Thicker materials tend accumulate near the mountains, while the fines are transported further. The total groundwater recharge, obtained from the water balance, is 1.560,93 l/s. Based on the record levels in 13 wells monitored by SENARA, static levels of the aquifer system were established.